2020
DOI: 10.1093/brain/awaa147
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and treating GRIN2A developmental and epileptic encephalopathy in mice

Abstract: NMDA receptors play crucial roles in excitatory synaptic transmission. Rare variants in GRIN2A encoding the GluN2A subunit are associated with a spectrum of disorders, ranging from mild speech and language delay to intractable neurodevelopmental disorders, including but not limited to developmental and epileptic encephalopathy. A de novo missense variant, p.Ser644Gly, was identified in a child with this disorder, and Grin2a knock-in mice were generated to model and extend understanding of this intractable chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 72 publications
6
70
0
Order By: Relevance
“…However, animals showed an enhancement in vertical exploration during the OF task and increased object exploration time during the NOR training, which led us to hypothesize that these animals explore the space or acquire the contextual information in a different way. Amador and colleagues generated a grin2A transgenic mouse expressing a grin2A mutant variant with reduced levels of GluN2A expression and a gain of function: these mice showed a complex neurological phenotype, with the most prominent features being hyperactivity, decreased anxiety-like, and repetitive behaviors (Amador et al, 2020). Altogether, these results raise the possibility that the extent in time and space of changes in GluN2A expression is responsible, at least in part, for behavioral abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, animals showed an enhancement in vertical exploration during the OF task and increased object exploration time during the NOR training, which led us to hypothesize that these animals explore the space or acquire the contextual information in a different way. Amador and colleagues generated a grin2A transgenic mouse expressing a grin2A mutant variant with reduced levels of GluN2A expression and a gain of function: these mice showed a complex neurological phenotype, with the most prominent features being hyperactivity, decreased anxiety-like, and repetitive behaviors (Amador et al, 2020). Altogether, these results raise the possibility that the extent in time and space of changes in GluN2A expression is responsible, at least in part, for behavioral abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Grin2A mutations that induce both a gain and a loss of function of the NMDAR were associated with complex syndromes that include, to a great extent, the occurrence of seizures (Endele et al, 2010;Lemke et al, 2013;Pierson et al, 2014;Yuan et al, 2014;Burnashev and Szepetowski, 2015;Swanger et al, 2016;Addis et al, 2017;Sibarov et al, 2017;Cardis et al, 2018;Punnakkal and Dominic, 2018;Strehlow et al, 2019;Amador et al, 2020;Mota Vieira et al, 2020). More recently, it has been shown that some grin2A mutant variants induced a decrease in GluN2A expression (Addis et al, 2017;Amador et al, 2020;Mota Vieira et al, 2020). In this work, we focused on the relationship between decreasing GluN2A expression and seizure onset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations